Optimasi Metode Microwave-Assisted Extraction (MAE) untuk Menentukan Kadar Flavonoid Total Ekstrak Etanol Kulit Pisang Kepok (Musa Paradisiaca.L) - Salsabila Khoerunniyssa; Danang Raharjo; Bagas Ardiyantoro (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Indonesia is a country that has a lot of banana diversity. One of the banana plants that is widely found in Indonesia is the Kepok banana (Musa Paradisiaca.L). Kepok banana skin has a very high content of flavonoids and phenols. Flavonoids are known as good antioxidants because they can find reactive oxygen species with the phenolic hydroxyl group that flavonoids have. The aim of this research was to determine the results of the optimization of the Microwave-Assisted Extraction (MAE) method on the total flavonoid content of kapok banana peel ethanol extract. Microwave-Assisted Extraction (MAE) was done to extraction flavonoid from ethanol extract of kepok banana peel (Musa Paradisiaca.L). The sample collected from Widoro village, Karangsambung sub-district, Kebumen regency. Optimum extraction condition was determined by the Response Surface Methodology (RSM). The Box- Behnken design (BBD) was used to evaluate the influence of 3 factors with 3 levels extraction that is power level (10%, 30%, 50%), ethanol concentration (50, 70, 96%), and extraction time (3, 5 and 7 minutes) with 15 different runs. The research showed that optimum extraction condition was at 24,14 % of power level, 66,26% ethanol concentration, and time extraction of 3,52 minutes with calculations from the Design Expert program, the total flavonoid content response was 8.491 Mg QE/g. The total flavonoid content value obtained experimentally was 8,246 Mg QE/g under condition of 30 % power level, 70% ethanol concentration, and time extraction of 5 minutes. Based on the result, total flavonoid content can be significantly increased by optimizing the MAE process use RSM.